নারীর আর্থ-সামাজিক উন্নয়ন ও ক্ষমতায়নে সিভিডিপি'র প্রভাব - বেগম, নূরুন্ নাহার (কুমিল্লা : বাংলাদেশ পল্লী উন্নয়ন একাডেমী (বার্ড), 2012)
Articles on the role of Comprehensive Village Development Programme (CVDP) in socio-economic development of women in Bangladesh.
বিবলিওগ্রাফী অন্তর্ভূক্ত (পৃ. ৬৯-৭০)
In Bengali.
Keywords: Comprehensive Village Development Programme (Bangladesh); Rural development projects -- Bangladesh; Women -- Bangladesh -- Social conditions; Women -- Bangladesh -- Economic conditions